Treatment of Palm Oil Mill Effluent by Mesophilic Anaerobic Digestion with Flocculant Addition - Sapari, Nasiman; Chew, Thean Yean; Yaziz, Mohammad Ismail (Universiti Putra Malaysia Press, 1996)
This paper presents research findings on the use of flocculants in the anaerobic digestion of palm oil mill ellluent (POME) under mesophilic conditions (37°C). Zetag 88N, a cationic polyacrylamide of high molecular density, was added to the digester at the beginning of the operation. The use of the flocculant enabled pelletization to occur in the digester within three months of start-up for the substrate which is difficult to granulate naturally. The effect of pelletization resulted in an increase in biomass concentration and produced a good solid-liquid separation within the digester, resulting in enhanced treatment performance and the ability to tolerate higher organic loads. Stable mesophilic anaerobic digestion can be operated up to a maximum organic loading rate of 19 kg chemical oxygen demand (COD) m-3 day-l (hydraulic retention time = 3.6 days)